2013
DOI: 10.1682/jrrd.2012.05.0097
|View full text |Cite
|
Sign up to set email alerts
|

Amputee Mobility Predictor-Bilateral: A performance-based measure of mobility for people with bilateral lower-limb loss

Abstract: Abstract-The Amputee Mobility Predictor (AMP) is an outcome measure designed to assess mobility and functional capabilities for people with unilateral lower-limb amputation. No comparable measure exists for those with bilateral lower-limb amputation (BLLA). The purpose of this study was to examine the utility of the AMP-Bilateral (AMP-B) to measure the ability to perform functional tasks related to participation in advanced skill activities in those with BLLA and to determine whether AMP-B scores correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The cohort of amputees reported in this study had a mean NISS of 40AE15, which we believe constitutes the highest severity of traumatic amputee injury in the available literature. 11,12 Despite this, upon completion of a comprehensive and intensive rehabilitation pathway, these patients had functional and mental health status comparable with that of the general population. Patient mobility is a critical component of successful rehabilitation and vital in aiding ADL.…”
Section: Discussionmentioning
confidence: 95%
“…The cohort of amputees reported in this study had a mean NISS of 40AE15, which we believe constitutes the highest severity of traumatic amputee injury in the available literature. 11,12 Despite this, upon completion of a comprehensive and intensive rehabilitation pathway, these patients had functional and mental health status comparable with that of the general population. Patient mobility is a critical component of successful rehabilitation and vital in aiding ADL.…”
Section: Discussionmentioning
confidence: 95%
“…The 6MWT can identify impairments of the musculoskeletal system that can affect ambulation ability such as weakness in the muscles that support ambulation (32). Chin et al reported that when older HDA patients are in good physical condition, they are successfully able to walk with a prosthesis in a community setting (10).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, individuals with bilateral above-knee amputations can only walk for short distances and have a high risk of falling 4 , 5 . Most importantly, climbing stairs requires individuals to use their upper body strength, basically pulling themselves up the stairs because the knee prostheses cannot generate extension torque as necessary to lift the body up the step 6 , 7 . Most individuals do not have the strength to perform this movement, as a result, they are unable to ascend stairs 7 .…”
Section: Introductionmentioning
confidence: 99%